2004
DOI: 10.1016/j.jm.2003.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Leader Political Skill and Team Performance

Abstract: The present study investigates the impact of the political skill of leaders on team performance. More specifically, this study examined the role of leader political skill in the performance of casework teams in a large state child welfare system. Team performance was operationalized as “permanency rate,” or the successful placement of children into legally final living arrangements (i.e., adoption, successor guardianship, or return to natural parents). After controlling for several contextually important facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
367
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(411 citation statements)
references
References 34 publications
8
367
0
11
Order By: Relevance
“…Ahearn et al (2004) found that leader political skill was positively related to team perfor-mance. Similarly, Treadway et al (2004) found that leader political skill positively predicted trust and job satisfaction and negatively predicted organizational cynicism through its positive relationship with perceived organizational support.…”
Section: Political Skillmentioning
confidence: 99%
“…Ahearn et al (2004) found that leader political skill was positively related to team perfor-mance. Similarly, Treadway et al (2004) found that leader political skill positively predicted trust and job satisfaction and negatively predicted organizational cynicism through its positive relationship with perceived organizational support.…”
Section: Political Skillmentioning
confidence: 99%
“…The perspective of the above participant is valid as it is easier for the head of a camel to pass through the eye of a niddle than for an organization to grow beyond the competence of its workforce (Ahearn, Ferris, Hochwarter, Douglas, & Ammeter, 2004;Collins 2009). …”
Section: Output Stagementioning
confidence: 99%
“…These include widespread changes to company structures resulting in more complex and challenging work environments for managers. With greater spans of control the manager role is increasingly concerned with the need to influence groups and social situations rather than monitoring the performance of individual subordinates (Ahearn, Ferris, Hochwarter, Douglas & Ammeter, 2004;Ferris, Witt & Hochwarter, 2001). Similarly, a growing emphasis on coaching, facilitating, and coordination of teams has meant that political skills have become more important to managers" ability to achieve their own individual objectives.…”
Section: Perceptions Of Politics: a Critical Evaluationmentioning
confidence: 99%
“…They argue that political skill affects the type of influence tactics people use and how effective they are. In a comparatively rare study using objective measures of team performance, Ahearn et al (2004) investigated the impact of leader political skill on how successful child welfare casework teams were at placing children into legally final living arrangements. They found that subordinate perceptions of their leader"s political skill predicted leader effectiveness ratings after controlling for leader demographic and social skill variables.…”
Section: Perceptions Of Politics: a Critical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation